Kontroversi dalam Tasawuf dan Mursyid - Salim Bela Pili (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2024)
The diversity of Sufi facial aspects, both in theoretical conceptualization (nadzariyah) and practical application within various orders (amaliyah), has led to perceptions, some of which carry negative connotations. The negative image of Sufism, emanating from the theoretical aspects of its teachings, is partly rooted in the intertextuality of concepts such as zuhud, faqir, and khalwat, which are often understood incomprehensively and devoid of contextualization. Consequently, these concepts suggest individual passivity and the practitioner's social detachment through escapism. The objective of this research is to provide an alternative portrayal counteracting the prevailing negative perceptions of Sufism. Additionally, it aims to establish the notion that positive perceptions of Sufism are propagated by the rightful murshid – a genuine Sufi expert who profoundly grasps the essence of authentic Sufism. Understanding one's position in life, the murshid is not a figure easily found amidst the multitude of contemporary scholars due to the numerous criteria that must be fulfilled, promising quality guidance for disciples. This exposition stems from qualitative research utilizing a Literature Review approach. Data collection techniques involve intensive examination of internal reference sources within the Sufi tradition/field of knowledge. The acquired data is subsequently expounded and interpreted analytically.